Synthesis, Characterization, and Ecotoxicology Assessment of Zinc Oxide Nanoparticles by In Vivo Models - Ileska M. Casiano-Muñiz; Melissa I. Ortiz-Román; Génesis Lorenzana-Vázquez; Félix R. Román-Velázquez (Nanomaterials, 2024)
The widespread use of zinc oxide nanoparticles (ZnO NPs) in multiple applications has increased the importance of safety considerations. ZnO NPs were synthesized, characterized, and evaluated for toxicity in Artemia salina and zebrafish (Danio rerio). NPs were characterized by X-ray diffraction (XRD), Fourier-transform infrared spectroscopy (FT-IR), and ultraviolet-visible (UV-Vis) spectroscopy. The hydrodynamic size and stability of the ZnO NP surface were examined using a Zetasizer. Characterization techniques confirmed the ZnO wurtzite structure with a particle size of 32.2 ± 5.2 nm. Synthesized ZnO NPs were evaluated for acute toxicity in Artemia salina using the Probit and Reed and Muench methods to assess for lethal concentration at 50% (LC50). The LC50 was 86.95 ± 0.21 μg/mL in Artemia salina. Physical malformations were observed after 96 h at 50 μg/mL of exposure. The total protein and cytochrome P450 contents were determined. Further analysis was performed to assess the bioaccumulation capacity of zebrafish (Danio rerio) using ICP-OES. ZnO NP content in adult zebrafish was greater in the gastrointestinal tract than in the other tissues under study. The present analysis of ZnO NPs supports the use of Artemia salina and adult zebrafish as relevant models for assessing toxicity and bioaccumulation while considering absorption quantities.